Periodontal Care as a Fundamental Step for an Active and Healthy Ageing - Carlo Cafiero; Marco Matarasso; Gaetano Marenzi; Vincenzo Iorio Siciliano; Loredana Bellia; Gilberto Sammartino (The Scientific World Journal)
In the industrialized part of the world, an increasing number of people live the old age without too many restrictions due to illness or physiological impairment. This group is known as the young elderly. On the contrary, a consistent part of seniors develops a greater number of medical conditions and become more and more dependent, these are the old elderly. The first cause of tooth lost in industrialized word is periodontitis that generally strikes people older than 40 years and determines serious detriment of the stomatognatic organ. Smoking and stress are risk factors for periodontitis that are common and shared between young, adult, and older age. Diabetes mellitus, obesity, and osteoporosis are very frequent pathological situations in older age. They have been identified as cofactors in the progression of periodontitis. Many dental associations recognize the importance of continued research on oral fluids diagnostics and welcome the development of rapid point-of-care tests providing accurate measurements of clinically validated biomarkers. At present, well-studied molecules associated with host response factors and with derived tissue destruction mediators have been proposed as diagnostic biomarkers for periodontitis detected in the oral fluids.